Domestic Violence in Black and White: Racialized Gender Stereotypes in Gender Violence - Fenton, Zanita E. (Columbia Journal of Gender and Law, 1998)
The media attention given to the criminal and civil trials of Orenthal James Simpson has focused the attention of mainstream society on the issues surrounding domestic violence. Unfortunately, instead of prompting greater awareness of the magnitude of the issues, the media and the actors in the legal proceedings manipulated stereotypes and obscured the issues of domestic violence. Through the lens of the media focus on the O.J. trials, the issue of domestic violence has implicitly become “black and white.” Literally, beliefs about justice in these cases were portrayed by media polls as divided by race. For example, a Los Angeles Times poll conducted near the end of the civil trial indicated that “71 % of whites said they thought Simpson committed the murders, while 70% of blacks said they thought he was innocent.” There were no polls broken down by gender. In fact, we don’t know if the polls that were done by race included proportional numbers of men and women of either race. Would it have been more or less significant if men and women (regardless of race) held the same views about the issues of domestic violence? There were also no polls broken down by income or social status. Would it have mattered if people’s belief in Simpson’s innocence or guilt correlated to their relative income? Most significantly, these polls did not reveal the basis for the responses of the pollees. Do we know if their perceptions of justice were based on race, or on gender, or on class, or on the available evidence, or on all of the above?